MOBILISASI ALAT BERAT PADA PROYEK PEMBANGUNAN RSUD TALAGA, MAJALENGKA - DENI A. NURYANA; ARIEF RIJALUDDIN (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2021)
Heavy equipment mobilization is an activity to bring project equipment to the project location based on the specified specifications. The choice of heavy equipment is something important and must be considered so that its use is efficient and effective because it will affect the productivity of the machine. In this Talaga RSUD construction project, there are several jobs that use heavy equipment such as piling work with drop hammers, excavating poor with excavators and casting with concrete pump trucks and cranes.